Rickettsia typhi central nervous system infection. (2020) - Talhelm, Collin F.; Helms, Jessica L.; Tran, Liem T.; Contreras, Brian X.; Stevens, Mark L.; Sierra-Hoffman, Miguel; Castro-Lainez, Miriam T.; Deliz, Rafael J.
Abstract: A 39 year-old male was residing along the south coast of Texas, the USA, presented with fever, myalgias, headaches, and weight loss for ten days. Symptoms and manifestations progressed to include nuchal rigidity, photophobia, hyponatremia, thrombocytopenia, and transaminitis despite the intravenous administration of ceftriaxone and azithromycin. A lumbar puncture performed in the Emergency Department yielded pleocytosis and glucose cerebrospinal fluid/serum ratio of 0.35, suggestive of meningoencephalitis. Conglomerate data raised the suspicion of meningitis secondary to a zoonotic acquired infection, which was later confirmed to be Rickettsia typhi . Doxycycline is the drug of choice for the suspected Rickettsia disease. After doxycycline administration, the patient improved and was discharged home asymptomatic.